1996
DOI: 10.1080/00071669608417861
|View full text |Cite
|
Sign up to set email alerts
|

Effect of egg turning and fertility upon the sodium concentration of albumen of the Japanese quail

Abstract: 1. The effects of egg turning and fertility upon sodium concentration of albumen of the Japanese quail is described for up to 72 h incubation. 2. For incubated eggs the sodium concentration of albumen adjacent to the yolk sac was lower than that from albumen next to the shell. Static incubation increased the magnitude of this difference, such that albumen adjacent to the yolk sac was substantially depleted of sodium. This was found at the yolk equator and the yolk vegetal pole of both fertilised and unfertilis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This value could reasonably be deemed representative for all sea turtles, as it is not very different from that reported for a freshwater turtle (92.5 mmol kg -1 ) [62], for avian albumen (approx. 82 mmol kg 21 ) [63], or for another report from loggerheads if we assume the total 'salts' reported were entirely sodium chloride (102 mmol kg 21 ) (calculated from [48]). Therefore, we will adopt 95.7 mmol kg 21 as the albumen sodium concentration for later calculations.…”
Section: Is the 'Water-limitation' Hypothesis Plausible From A Water Balance Perspective?mentioning
confidence: 99%
“…This value could reasonably be deemed representative for all sea turtles, as it is not very different from that reported for a freshwater turtle (92.5 mmol kg -1 ) [62], for avian albumen (approx. 82 mmol kg 21 ) [63], or for another report from loggerheads if we assume the total 'salts' reported were entirely sodium chloride (102 mmol kg 21 ) (calculated from [48]). Therefore, we will adopt 95.7 mmol kg 21 as the albumen sodium concentration for later calculations.…”
Section: Is the 'Water-limitation' Hypothesis Plausible From A Water Balance Perspective?mentioning
confidence: 99%
“…Hence, in unturned eggs, they suggested, a depletion of sodium from the layer of albumen adjacent to the blastoderm, due to a lack of`stirring', would result in insuf®cient sodium for this process. Latter and Baggott (1996) investigated this proposal directly using eggs of the Japanese quail incubated from 24 to 72 hours. They tested the speci®c predictions that sodium would be depleted from the albumen adjacent to the yolk sac and that this would occur in eggs only where active sodium transport occurred, i.e.…”
Section: Effect Of Egg Turning On the Ionic Composition Of Sef Albummentioning
confidence: 99%
“…Latter and Baggott (1996) found that unincubated eggs had a low sodium concentration in the albumen adjacent to the vitelline membranes. Egg turning increased the sodium concentration at this location by the same magnitude throughout the period of SEF production, whereas unturned eggs retained this 'depleted layer'.…”
Section: Introductionmentioning
confidence: 99%